Ketamine administration for acute painful sickle cell crisis: A randomized controlled trial. (21st September 2021) - Alshahrani, Mohammed S.; AlSulaibikh, Amal H.; ElTahan, Mohamed R.; AlFaraj, Sukayna Z.; Asonto, Laila P.; AlMulhim, Abdullah A.; AlAbbad, Murad F.; Almaghraby, Nisreen; AlJumaan, Mohammed A.; AlJunaid, Thamir O.; Darweesh, Moath N.; AlHawaj, Faisal M.; et al.
Abstract: Objective: The objective was to evaluate the efficacy and safety of single‐dose ketamine infusion in adults with sickle cell disease (SCD) who presented with acute sickle vasoocclusive crisis (VOC). Methods: This study was a parallel‐group, prospective, randomized, double‐blind, pragmatic trial. Participants were randomized to receive a single dose of either ketamine or morphine, infused over 30 min. Primary outcome was mean difference in the numerical pain rating scale (NPRS) score over 2 h. NPRS was recorded every 30 min for a maximum of 180 min and secondary outcomes were cumulative dose of opioids, emergency department (ED) length of stay, hospital admission, change in vital signs, and drug‐related side effects. Authors performed the analysis using intention‐to‐treat principle. Result: A total of 278 adults with SCD and who presented with acute sickle VOC participated in this trial. A total of 138 were allocated to the ketamine group. Mean (±standard deviation [SD]) NPRS scores over 2 h were 5.7 (±2.13) and 5.6 (±1.90) in the ketamine and morphine groups. The ketamine group received significantly lower cumulative doses of morphine during their ED stay (mean ± SD = 4.5 ± 4.6 mg) than of the morphine group (mean ± SD = 8.5 ± 7.55 mg). Both groups had similar rates of hospital admission: 6.3% in the ketamine group had drug‐related side effects compared to 2.2% in the morphine group. Conclusion: Early use of ketamine in adults with VOC resulted in a meaningful reduction in pain scores over a 2‐h period and reduced the cumulative morphine dose in the ED with no significant drug‐related side effects in the ketamine‐treated group.